Regulation of active sodium and potassium transport in the distal colon of the rat. Role of the aldosterone and glucocorticoid receptors. - Turnamian, S G (1989)
To determine whether mineralocorticosteroids and glucocorticosteroids have specific effects on colonic electrolyte transport, we compared the effect of aldosterone and RU 28362, a glucocorticoid receptor-specific agonist that does not bind to the aldosterone receptor, on unidirectional Na, Cl, and K fluxes across isolated mucosa of the rat distal colon. Continuous infusion of aldosterone for 7 d produced changes in four specific transport processes: induction of both active electrogenic, amiloride-sensitive sodium absorption and active electrogenic potassium secretion, enhancement of active electroneutral potassium absorption, and inhibition of electroneutral Na-Cl absorption, the predominant transport process in this epithelium. In contrast, continuous infusion of RU 28362 for 1-11 d produced a sustained increase in electroneutral Na-Cl absorption. This glucocorticoid receptor-specific agonist did not induce electrogenic sodium absorption nor affect either potassium absorption or secretion. These studies demonstrate that aldosterone (i.e., mineralocorticoid) and glucocorticoid receptors modulate separate and specific changes in active sodium and potassium transport. These results suggest that other glucocorticoids (e.g., dexamethasone, methylprednisolone) are not glucocorticoid receptor-specific and that their effects on electrogenic sodium absorption and potassium transport most likely represent the binding of these agonists to the aldosterone receptor.